Searching for justice : an autobiography - Kaufman, Fred, 1924-2023 (Osgoode Society for Canadian Legal History., 2005)
Searching for Justice is Kaufman's remarkable story in his own words. It is the tale of adversity overcome in a crucial period of Canadian legal history.